City and Art Forum. - Abora, Emel; Poyrazoglu, Tuna; Görgün, Melih; Mimar sinan Fine Arts, Instanbul (Instanbul : Mimar Sinan Fine Arts Univesity, 2009)
Aksungur, Rahmi ; Asselbergs, Teike ; Austin, Tricia ; Bast, Gerald ; Butler, John ; Delfos, Carla ; Dervisoglu, Gökçe ; Dunhill, Mark ; Ebert, Lars ; Featherstone, Sarah ; Gansing, Kristoffer ; et al.
Publication of 'City and Art Forum' organised within the scope of the City and Art Project between 6-8 March in Istanbul, 2009.
boek